Antenatal Care Bundle for Preventing Stillbirths: Proposed Intervention by Stillbirth Society of India - Manju Puri; Tamkin Khan; Asna Ashraf; Bharti Sharma; Achla Batra; Amrita Chaurasia; Aradhana Singh; Ayesha Ahmad; Bushra Fatima; Harpreet Kaur; Kiran Pandey; Manisha Kumar; et al. (Indian Journal of Community Medicine)
Antenatal Care Bundle” presents evidence-based antenatal care interventions aimed at reducing stillbirths, developed by the Stillbirth Society of India. The interventions are designed to complement WHO recommendations, focusing on risk assessment, maternal and fetal monitoring, and management of fetal growth restriction, particularly in low-resource settings. They are intended to be adopted by all the practitioners to provide standard care to every pregnant woman for optimal outcomes. Each section of this bundle has undergone extensive discussion followed by consensus. The recommendations have been graded according to the level of evidence-based as recommended by NICE guidelines.